POLITIK HUKUM UNDANG-UNDANG NOMOR 33 TAHUN 2014 TENTANG JAMINAN PRODUK HALAL - El-Razy, K.M. Ridho; SA, Romli (Muamalah, 2019)
Abstract This study is entitled "Implementation of Law Number 33 Year 2014 Regarding Halal Product Guarantee (Legal Political Studies)." There are several main driving factors for this research. First, the legislation regulating or relating to halal products in their implementation in the field has not provided legal certainty and legal guarantees for Muslims regarding food and other products such as food products that are not packaged. Such conditions make Muslims find it difficult to differentiate between what is halal and what is haram, raising doubts about birth and inner unrest in consuming food and using other products. Second, the production and distribution of products are difficult to control as a result of increasing food technology, genetic engineering, irradiation, and biotechnology. Third, there are many asymmetries. s to determine the halal status of food, medicines and cosmetics, which in this case is called the Halal Product Guarantee Agency, abbreviated with BPJPH which must be born no later than 3 (three) years from the enactment of the law; but the reality has yet to materialize, even though the auditor is still running by LPPOM MUI and it is protected by the law, however even though LPPOM MUI is still constrained by various things, especially synchronization of various related agencies has not yet been carried out. Keyword: Franchise, Business, Islamic Law